Insights into the ecology, genetics and distribution of Lucanus elaphus Fabricius (Coleoptera: Lucanidae), North America's giant stag beetle. Issue 4 (17th April 2017) - Ulyshen, Michael D.; Zachos, Louis G.; Stireman, John O.; Sheehan, Thomas N.; Garrick, Ryan C.
Abstract: Little is known about the biology or conservation status of Lucanus elaphus Fabricius in North America despite well‐documented declines of a related species, Lucanus cervus (L.), in Europe. This study provides information critical to developing conservation plans for L. elaphus including the species' larval substrate requirements, genetic data and range‐wide estimates of habitat suitability. In Mississippi floodplain forests, larval L. elaphus were recovered from a wide range of log sizes and rot types and were either found tunnelling within the wood or feeding beneath logs at the soil–wood interface. The species appears to require 1–2 years to complete development, exhibits a 1:1 sex ratio and is parasitised by Zelia vertebrata (Say) (Diptera: Tachinidae). Flight intercept traps placed at three heights at both the edge and interior of hardwood‐dominated forests in Georgia yielded six adult male L. elaphus, all of which were captured in traps placed at 15 m on the forest edge. Because L. elaphus larvae are morphologically indistinguishable from related species, DNA sequence data from the mitochondrial cytochrome oxidase I gene were generated to facilitate molecular identification. Genetic data revealed modest intra‐specific variation, with up to 1.3% sequence divergence among haplotypes sampled from the same forest. Based on assembled occurrence records, ecological niche models suggest that environmental conditions are suitable for L. elaphus across much of the southeastern United States, provided that adequate lowland forest cover and dead wood substrates are available.